1995
DOI: 10.1037/0882-7974.10.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of everyday problem solving in older adults.

Abstract: This study investigated individual differences in older adults' everyday problem-solving performance using 3 instruments. Past research, typically using only single measures, has yielded a multitude of findings regarding age effects in everyday problem solving. The present sample consisted of 111 older adults (44 men, 67 women) who ranged in age from 68 to 94 years. Confirmatory factor analyses revealed that, within each of the 3 instruments, subscales representing particular content domains could be reliably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 58 publications
(138 reference statements)
10
124
0
2
Order By: Relevance
“…In the Georgia Centenarian Study, which included participants in their sixties, eighties, and hundreds, age was strongly negatively associated with fluency in two studies (Poon et al, 1992;Holtsberg et al, 2002), although Holtsberg et al (2002) reported that age differences were actually confined to the best educated participants (perhaps because well-educated 60 year olds were more like Denney's middleaged subjects and had not yet experienced declines). Findings similar to those of Holtsberg et al's less educated adults were reported by Marsiske and Willis (1995). The latter study found no relationship between age and fluency (r ¼ À.08) on the Denney and Pearce (1989) task.…”
Section: A Accuracy/effectiveness Studiessupporting
confidence: 79%
See 2 more Smart Citations
“…In the Georgia Centenarian Study, which included participants in their sixties, eighties, and hundreds, age was strongly negatively associated with fluency in two studies (Poon et al, 1992;Holtsberg et al, 2002), although Holtsberg et al (2002) reported that age differences were actually confined to the best educated participants (perhaps because well-educated 60 year olds were more like Denney's middleaged subjects and had not yet experienced declines). Findings similar to those of Holtsberg et al's less educated adults were reported by Marsiske and Willis (1995). The latter study found no relationship between age and fluency (r ¼ À.08) on the Denney and Pearce (1989) task.…”
Section: A Accuracy/effectiveness Studiessupporting
confidence: 79%
“…This is consistent with an analysis conducted by Marsiske and Willis (1995), who administered two social problem-solving measures (i.e., Cornelius & Caspi, 1987;Denney & Pearce, 1989) and one instrumental measure (Willis & Marsiske, 1995) in a single sample of older adults. Marsiske and Willis (1995) found no relationship between social problems and age, but a negative age relationship with the instrumental task. Sinnott (1989b), among others, has suggested that qualitative aspects of everyday problem solving require at least as much attention as actual performance.…”
Section: A Accuracy/effectiveness Studiessupporting
confidence: 61%
See 1 more Smart Citation
“…Our findings suggest that the well-and ill-defined measurement approaches are distinct but related, and both may be important in predicting older adults' everyday functional competence, above and beyond the more context-free measures of cognition typically included in the adult development literature. Expressed differently, these findings can be used to further argue that everyday cognition should not be considered unitary but instead as a multidimensional construct (e.g., Marsiske & Willis, 1995). Thus, the study of everyday cognition will further benefit if a multiple-measurement framework, including both welland ill-defined measures, is incorporated into future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults were also reported to endorse more effective problem solving in comparison to middle-aged and younger adults [11]. Marsiske and Willis [12] supported the idea of multidimensionality of everyday problem solving. Based on older adults' reporting about having difficulties with tasks of cognition in a laboratory setting while feeling apparent efficacy managing everyday lives, Marsiske and Willis pointed out "an intuitive paradox".…”
Section: Introductionmentioning
confidence: 67%